Epilepsy, gut microbiota, and circadian rhythm - Wang, Yao; Zhuo, Zhihong; Wang, Huaili (Frontiers in Neurology, 2023)
In recent years, related studies have found the changes of gut microbiota in patients with epilepsy. In addition, impaired sleep and circadian patterns are common symptoms of epilepsy. Moreover, the types of seizures have circadian rhythm. Numerous reports indicate that the gut microbiota and its metabolites have circadian rhythms. This review will describe changes in the gut microbiota in clinical and animal studies under epilepsy and circadian disruption conditions, respectively. The aim is to determine the commonalities and specificities of alterations in gut microbiota and their impact on disease occurrence under conditions of epilepsy and circadian disruption. Although clinical studies are influenced by many factors, the results suggest that there are some commonalities in the changes of gut microbiota. Finally, we discuss the links among epilepsy, gut microbiome, and circadian rhythms, as well as future research that needs to be conducted.